Dilema Integrasi Tasawuf dan Psikoterapi dalam Kelanjutan Islamisasi Psikologi - Naufil Istikhari ('Anil Islam: Jurnal Kebudayaan dan Ilmu Keislaman, 2016)
An ambitious integration of Sufism concepts and practices into modern psychotherapy is inseparably under influence from the second half 20th century trend of the islamization of psychology in the Muslim world. To some aspects, such integration has been highly successful. However, such integration deals with an eclectic theoretical dilemma between sufism and psychotherapy, since the former is regarded as spiritual-transcendental oriented for getting total submission to God, while the latter is not invariably ‘spiritual’ because it often involves manipulation and simulation as psychotherapy procedures. The mystic experience of Sufism is wordlessly unsaid, and it is almost impossible to be scientifically measured. In other side, the counseling and therapy need certain assessments, partly, in strict ways. Since having an ‘exclusive’ character in its practical dimension, Sufism is dealing with a paradigmatic dilemma in providing certain procedures for psychotherapy. This study is to depict such dilemma and its influence on the modern islamization of psychology.